1974
DOI: 10.1128/jb.117.3.960-964.1974
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Mutagenic Action of Black Light (325 to 400 nm) on Haemophilus influenzae in the Presence of Air

Abstract: Near-ultraviolet (UV) light (325 to 400 nm), in the presence of air and the absence of exogenous photosensitizing compounds, is lethal and mutagenic for Haemophilus influenzae. The lethal effect is the same for both wild type and streptomycin-resistant mutants, indicating that the mutants are not selected by the irradiation. The inactivation and mutagenicity show a large shoulder, suggesting the existence of repair systems. Filters were used to eliminate the possibility of short-UV irradiation. The effective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…We have attempted to measure far-UV coming through pyrex glass and find the material opaque to these wavelengths. Fourth, in a single experiment with the strain AB2463, we used a napthalene filter (Blanc et al, 1976;Cabrera-Juarez and Espinosa-Lara, 1974) and observed that following a 1.2 Jm-' x dose of unfiltered near-UV survival was approximately 55% while filtering yielded 100% survival. Following a 1.8 Jm-2 x dose of near-UV, survival with filtered near-UV was 23.3% while survival with unfiltered near-UV was 17.8%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have attempted to measure far-UV coming through pyrex glass and find the material opaque to these wavelengths. Fourth, in a single experiment with the strain AB2463, we used a napthalene filter (Blanc et al, 1976;Cabrera-Juarez and Espinosa-Lara, 1974) and observed that following a 1.2 Jm-' x dose of unfiltered near-UV survival was approximately 55% while filtering yielded 100% survival. Following a 1.8 Jm-2 x dose of near-UV, survival with filtered near-UV was 23.3% while survival with unfiltered near-UV was 17.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of bacterial cell populations to inactivation by both far-UV (Tyrrell et al, 1972) and near-UV varies with growth phase (Cabrera-Juarez and Espinosa-Lara, 1974;Hartman and Eisenstark, 1978;Mackay et a/., 1976). Our results and those of others (Peak, 1970;Webb, 1977) show that resistance to near-UV increases exponentially when the cells enter the transition from the exponential to stationary growth phase (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation by blacklight (BL; 300-400 nm) has been investigated in procaryotes (Cabrera-Juarez and Espinosa-Lara, 1974;Eisenstark, 1970;Hollaender, 1943;Kock et al, 1976;Peak, 1970;Lorenz, 1970;Webb and Tai, 1970) and eucaryotes (Blanc et a!., 1976;Elkind and Han, 1977;Hollaender and Emmons, 1941). BL inactivation of transforming DNA (Blanc et ul., 1976;Cabrera-Juarez, 1964;Peak et al, 1973a, b, c).…”
Section: Introductionmentioning
confidence: 99%
“…BL inactivation of transforming DNA (Blanc et ul., 1976;Cabrera-Juarez, 1964;Peak et al, 1973a, b, c). and evidence for mutagenesis by BL in Escherichiu coli (Kubitschek, 1967;Webb and Malina, 1970) and Hapmophilus influenme (Cabrera-Juarez and Espinosa-Lara, 1974) have implicated DNA as the target for lethal damage. However, mutagenesis by BL irradiation could not be demonstrated in spores of either Neurospora crassu (Tuveson and Satterthwaite, 1976) or Trichophyton mentugrophytes (Hollaender and Emmons, 1941).…”
Section: Introductionmentioning
confidence: 99%